Measuring the Root Determinants of Income Level and the Impact on the Financial Literacy of MSME Actors - Anton Priyo Nugroho; Syawal Zakaria; Yulianti Yulianti; Maryam Sangadji; Ninik Endang Purwati (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This research was conducted to see the effect of the variables of education level, gender, and business time on financial literacy with income level as an intervening variable in Kalongan Village MSMEs. Descriptive quantitative approach used in research. The population in this study were SMEs in the Kalongan Village area, totaling 116 SMEs and the sampling technique used was a census. The research instrument was tested using validity and reliability tests which were then processed with multiple linear regression analysis coupled with the path test/sobelt test in the SPSS program. The results of the analysis illustrate that (1) the level of education has a positive and significant effect on the level of income; (2) gender has a positive and significant effect on income levels; (3) business time has a positive and significant effect on income levels; (4) income level has a positive and significant effect on financial literacy; (5) gender has a positive and significant effect on financial literacy; (6) business time has a positive and significant effect on financial literacy; (7) The level of income has a positive and significant effect on financial literacy; (8) Income level is not able to mediate the relationship between education level and financial literacy; (9) Income level is unable to mediate gender relations on financial literacy; and (10) income level is not able to mediate the relationship between business time and financial literacy